2019
DOI: 10.1016/j.jsxm.2019.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Motor Function and Perception of Health in Women with Provoked Vestibulodynia

Abstract: Background: Provoked vestibulodynia (PVD) is a prevalent and disabling condition in women that may be associated with reduced quality of life and impairment of physical functioning. Aim: To investigate whether women with PVD have different motor functions, posture and breathing patterns, and whether they perceive their physical health differently, compared with asymptomatic controls. Methods and Main Outcome Measure: The Standardized Mensendieck Test (SMT) and the Medical Outcomes Study 36-Item Short-Form Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…On the other hand, years passed since the vulvodynia diagnosis correlated positively with quality of life, but the correlation was significant only in the environmental domain. In the study by Naetss et al [ 58 ], the quality of life of patients with provoked vestibulodynia was compared to a healthy control group using the SF-36 questionnaire. Healthy controls had statistically significantly higher scores in every QOL domain, except the physical functioning and emotional domains, indicating that chronic vulvar pain decreases quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, years passed since the vulvodynia diagnosis correlated positively with quality of life, but the correlation was significant only in the environmental domain. In the study by Naetss et al [ 58 ], the quality of life of patients with provoked vestibulodynia was compared to a healthy control group using the SF-36 questionnaire. Healthy controls had statistically significantly higher scores in every QOL domain, except the physical functioning and emotional domains, indicating that chronic vulvar pain decreases quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Recovering the functionality of the pelvic floor, in term of awareness, contraction, relaxation, and normal tone, is one of the most important points of physical treatment. According to other studies [ 35 , 36 ], the present one used both active PFMs contraction and active PFMs relaxation to achieve a reduction in tone and an improvement of the awareness of the pelvic floor [ 35 – 37 ]. Likewise, some authors added the simultaneous intervention of global muscle relaxation and breathing techniques to their studies [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women with PVD show a lower score of perception of general health compared to controls [ 37 ]. Based on the SF-36 results, Naess et al indicated the perceived impact of PVD on these women’s lives in their study [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations